Web-based parking information system - Wee, Ai Cing (Universiti Malaysia Sarawak (UNIMAS), 2014)
Web-Based Parking Information System is developed to provide a graphical map interface module which provides parking patrons real time car parking space information in a shopping mall. The parking space information is based on a simulation to generate the number of parking lots availability. Parking patrons are able to get the information on the actual parking space availability before reaching the shopping centre. Therefore, parking patrons or customer of the shopping mall can actually know whether the parking lot is occupied or empty based on the information given. Subsequently, this can prevent their frustration if there is no parking space available during peak hour like sales promotions, weekend, lunch time and dinner time. In addition, this system can provide the latest information of promotions events in the shopping mall for parking patrons to get a free parking or discounted parking based on the terms and conditions provided.